2013
DOI: 10.1136/bcr-2012-008475
|View full text |Cite
|
Sign up to set email alerts
|

Crown fracture of the mandibular second primary molars in a 4-year-old child

Abstract: Dental traumas are highly prevalent lesions in primary teeth, but crown root fractures are rare. Mostly anterior tooth segment is more commonly involved. Posterior crown root fractures are very rare. A 4-year-old girl reported to our paediatric dentistry department with a 10-day history of severe pain and discomfort in both right and left posterior teeth region. The child was suffering from severe and continuous pain and was unable to chew food. After an examination a fracture was noticed in intraoral periapic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…Also, there are a lot of case report discussing posterior tooth fracture due to trauma in primary dentition. [16,17] A report by Gonzalez-Lopez et al [18] discusses similar management of tooth fracture in which the palatal gingiva of the fractured maxillary premolar was remodeled and later porcelain fused to metal crown was placed over the tooth. The study at 7 year follow up showed satisfactory esthetics and functional outcomes with good periodontal health.…”
Section: Discussionmentioning
confidence: 99%
“…Also, there are a lot of case report discussing posterior tooth fracture due to trauma in primary dentition. [16,17] A report by Gonzalez-Lopez et al [18] discusses similar management of tooth fracture in which the palatal gingiva of the fractured maxillary premolar was remodeled and later porcelain fused to metal crown was placed over the tooth. The study at 7 year follow up showed satisfactory esthetics and functional outcomes with good periodontal health.…”
Section: Discussionmentioning
confidence: 99%